"Got to build that trust": the perspectives and experiences of Aboriginal health staff on maternal oral health - Ariana C. Kong; Mariana S. Sousa; Lucie Ramjan; Michelle Dickson; Joanne Goulding; Kylie Gwynne; Folau Talbot; Nathan Jones; Ravi Srinivas; Ajesh George (BMC, 2020)
Abstract Background In Australia, models of care have been developed to train antenatal care providers to promote oral health among pregnant women. However, these models are underpinned by Western values of maternity care that do not consider the cultural needs of Aboriginal and Torres Strait Islander women. This study aimed to explore the perceptions and experiences of Aboriginal health staff towards oral health care during pregnancy. It is part of a larger program of research to develop a new, culturally safe model of oral health care for Aboriginal women during pregnancy. Methods A descriptive qualitative methodology informed the study. Focus groups were convened to yarn with Aboriginal Health Workers, Family Partnership Workers and Aboriginal management staff at two antenatal health services in Sydney, Australia. Results A total of 14 people participated in the focus groups. There were four themes that were constructed. These focused on Aboriginal Health Workers and Family Partnership Workers identifying their role in promoting maternal oral health, where adequate training is provided and where trust has been developed with clients. Yet, because the Aboriginal health staff work in a system fundamentally driven by the legacy of colonisation, it has significantly contributed to the systemic barriers Aboriginal pregnant women continue to face in accessing health services, including dental care. The participants recommended that a priority dental referral pathway, that supported continuity of care, could provide increased accessibility to dental care. Conclusions The Aboriginal health staff identified the potential role of Aboriginal Health Workers and Family Partnership Workers promoting oral health among Aboriginal pregnant women. To develop an effective oral health model of care among Aboriginal women during pregnancy, there is the need for training of Aboriginal Health Workers and Family Partnership Workers in oral health. Including Aboriginal staff at every stage of a dental referral pathway could reduce the fear of accessing mainstream health institutions and also promote continuity of care. Although broader oral health policies still need to be changed, this model could mitigate some of the barriers between Aboriginal women and both dental care providers and healthcare systems.